A review on concrete fracture energy and effective parameters. (June 2019) - Khalilpour, S.; BaniAsad, E.; Dehestani, M.
Abstract: This paper presents a discussion on the subject of fracture energy of concrete and effective parameters. Therefore, it serves as an overview of the available approaches in determining the fracture energy. It also includes experimental methods which form the basis for measuring the fracture energies obtained from work of fracture (GF ) and size effect models (Gf ) and thus provides a comparison between different models. Furthermore, the behavior of the load-displacement curve, factors affecting the fracture energy and the crack path in the specimen are discussed. In order to build a background for the current understanding of fracture energy, references from both former and present authors are included to tie the subject together within the course of time.